The Quistclose trust : critical essays - Swadling, William (Hart, 2004)
The decision of the House of Lords in Twinsectra v Yardley (2002) has refocused attention on the Quistclose trust (Barclays Bank v Quistclose Ltd [1970] AC 567). The purpose of these essays is to explore the supposed foundations of the trust and subject them to a searching analysis.